Unexpected supply effects of quantitative easing and tightening - Stefania D'Amico; Tim Seida (Federal Reserve Bank of Chicago, 2020)
To analyze the evolution of quantitative easingís (QE) and tighteningís (QT) eects across consecutive announcements, we focus on their unexpected component. Treasury yield sensitivities to QE and QT supply surprises do not fall monotonically over time, thus later announcements seemed to remain powerful; yield sensitivities to QT surprises are on average larger than sensitivities to QE surprises, implying supply eects did not diminish during periods of market calm amid economic expansion; Önally, yield sensitivities are ampliÖed by the amount of interest-rate uncertainty prevailing before the announcement, implying that turning points in the balance sheet policy tended to elicit larger reactions.
Keywords: E43; E44; E52; E58; 330; Balance sheet policy surprises; quantitative easing and tightening; asset supply effects